La nueva fuerza de trabajo en México : equipos de trabajo y eficiencia en las plantas automotrices de exportación - Ramírez, José Carlos (El Colegio de México A.C., 1996)
This paper concerns the microeconomic changes experienced by Northern Mexico's motor facilities while applying Just in Time/Total Quality Control manufacturing systems (jit/tqc). These changes are particularly related to the use of work teams (Wts) on the shop floor since, as will be shown later, it is a critical mechanism by which a plant engaged in implementing jit/tqc improves its efficiency indexes.The purpose of this paper is to provide support for our hypothesis, which states that the benefits from using Wts, and more generally from introducing jit/tqc are correlated with the level of automation, capital ownership, type of process and product, age and flexiblity of the plant.